The House That Children Built - Coleman, Marion Tolbert; Texas Univ., Austin. Hogg Foundation for Mental Health ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Casa de Esperanza, Incorporated, is a program which provides residential care to severely disturbed children, ages birth to 6 years. The philosophy of the program is to provide care to the disturbed child and counseling to the parents so that the child may return to the parental home once the crisis is past. The children are cared for in shelter houses with an emphasis on emotional attachment to the caregivers and consistency of caregiving. Casa staff attempt to build long-term relationships with the children which will continue after the children are reunited with their families. The ultimate goal of the program is to provide a continuum of care that can take the most disturbed child through a series of decreasingly structured environments to a point at which the child can function in a setting as close to normal as possible. Components of the program include parent/after care services, psychological services, the developmental center, the therapeutic nursery, medical clinic, foster homes, and therapeutic foster care. (The booklet contains vignettes describing the staff and particular children.) (ABL)
Availability: Hogg Foundation for Mental Health, University of Texas, Austin, TX 78713-7998.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Abuse; Counseling Services; Emotional Disturbances; Family Problems; Infants; Intervention; Mental Disorders; Parent Child Relationship; Parenting Skills; Psychotherapy; Residential Programs; Young Children; Reports, General